Physiological Predictors of Maximal Incremental Running Performance - Lanferdini, Fábio J.; Silva, Edson S.; Machado, Esthevan; Fischer, Gabriela; Peyré-Tartaruga, Leonardo A. (Frontiers in Physiology, 2020)
Purpose: The aim of this study was to verify whether physiological components [vertical jumps (Squat Jump–SJ and Countermovement Jump-CMJ), running economy (RE), metabolic cost (CMET), first and second ventilatory threshold (VT1 and VT2) maximal oxygen uptake (VO2MAX)] can predict maximal endurance running performance. Methods: Twenty ♂ runners performed maximal vertical jumps, submaximal running at constant speeds and maximal incremental running test. Previously, we measured anthropometric parameters (body mass and height) and registered the training history and volume. SJ and CMJ tests were evaluated prior to running tests. Initially, the oxygen uptake (VO2) was collected at rest in the orthostatic position for 6 minutes. Soon after, a 10-minute warm-up was performed on the treadmill at 10 km·h-1, followed by two 5-min treadmill rectangular tests at 12 and 16 km·h-1 monitored by a gas analyzer. After that, the runners performed a maximal incremental test, where the VT1, VT2 and VO2MAX were evaluated, as well as the maximum running speed (vVO2MAX). Thus, RE and CMET were calculated with data obtained during rectangular running tests. Multivariate stepwise regression analyses were conducted to measure the relationship between independent variables (height and power of SJ and CMJ; RE and CMET 12 and 16 km·h-1; VT1, VT2 and VO2MAX), as predictors of maximal running performance (vVO2MAX), with significance level at α=0.05. Results: We found that VO2MAX and RE at 16 km·h-1 predict 81% of performance (vVO2MAX) of long-distance runners (p<0.001). Conclusion: The main predictors of the maximal incremental running test performance were VO2MAX and RE.